Analisis Laporan Keuangan Sebagai Dasar Penilai Kinerja Keuangan Pada UKM CV. Citra Mandiri Keripik Kota Batu - Yance Mea Tahu; Dwi Anggarani; Khojanah Hasan (CV. ITTC INDONESIA, 2025)
Financial statements are documents used to describe a company's financial condition and performance over a specific period. The purpose of financial statement analysis is to assist in decision-making regarding the company's future. Analyzing financial statements reveals a company's strengths and weaknesses. The research approach used was qualitative and descriptive. The results indicate that CV Cita Mandiri Keripik Kota Batu has not been able to generate sufficient profits from existing sales. A higher net profit margin indicates a better performance by CV Cita Mandiri Keripik Kota Batu in effectively utilizing sales to generate profits. This situation is unfavorable for CV Cita Mandiri Keripik Kota Batu because the profits obtained do not meet general company standards.